Students’ Perception toward Vocabulary Mastery - Mutaat Mutaat; Radik Darmawan (Jurnal Pendidikan Bahasa, 2022)
The present study tries to identify the students’ perceptions toward vocabulary mastery of the literature students departments. There are 40 students who are recruited voluntarily to participate in the study. The students are actively learning students in the college. The instrument used in the present study is questionnaire. The use of questionnaire is to elicit the students’ perception on the vocabulary mastery and the other relevant factors affecting vocabulary mastery. The findings indicate that basically, the students have varied perceptions on the vocabulary taught to them. The finding also shows that the students prefer to learn vocabulary in context, for instance, the students can learn vocabulary while reading novel, short story, or the other reading materials, and not from the conversation, or listening material. The students are also found that they prefer to learn vocabulary, which are related to business, health, tourism, and technology. Lastly, they also prefer to learn vocabulary, which are closely related to their occupational background.